Growth of Betung Bamboo (Dendrocalamus asper) and Food Crop Production Under Agroforestry Bamboo Systems - Hani, Aditya; Suryanto, Priyono; Murniati, Murniati; Widiyatno (Jurnal Manajemen Hutan Tropika, 2024)
One of the main species in community forests is betung bamboo (Dendrocalamus asper). Optimizing land use under bamboo can be achieved by cultivating food crops. This research aimed to determine the growth of betung bamboo and the production of food crops. The experimental design used a split plot design with four cultivation patterns as the main plots: agroforestry bamboo pattern i.e. agroforestry bamboo + rice (P1), agroforestry bamboo + rice + cassava (P2), agroforestry bamboo + rice + taro (P3), and mixed food crops (rice + cassava + taro) (P4), while the subplots were rice varieties: rindang 2 (V1), protani (V2), and unsoed (V3). The observed parameters were bamboo growth, soil fertility, and food crop production. The results showed that seven-year-old betung bamboo had an average of 6.01 mature stems per clump, an average plant height of 7.23 m, and a stem diameter of 7.12 cm. The numbers of young stems and shoots per clump was 1.45 and 3.71. The highest betung bamboo growth was in the agroforestry pattern (length: 8,49 m, diameter: 7.17 cm, thickness: 1.95, total weight: 21.31 kg). The highest rice yield was observed in the P2V1 treatment (4.17 kg). The highest cassava tuber yield per plant was observed in P4 (2.12 kg). The taro tuber yield was relatively higher in the agroforestry pattern with a distance of >1 m from the bamboo clump (0.52 kg plant-1). The land equivalent ratio (LER) and area time equivalent ratio (ATER) of bamboo and food crop agroforestry have a value above 1, so it is more efficient in land.